2D Molybdenum Sulfide‐Based Materials for Photo‐Excited Antibacterial Application. Issue 13 (13th April 2022) - Chen, Fangqian; Luo, Yue; Liu, Xiangmei; Zheng, Yufeng; Han, Yong; Yang, Dapeng; Wu, Shuilin
Abstract: Bacterial infections have seriously threatened human health and the abuse of natural or artificial antibiotics leads to bacterial resistance, so development of a new generation of antibacterial agents and treatment methods is urgent. 2D molybdenum sulfide (MoS2 ) has good biocompatibility, high specific surface area to facilitate surface modification and drug loading, adjustable energy bandgap, and high near‐infrared photothermal conversion efficiency (PCE), so it is often used for antibacterial application through its photothermal or photodynamic effects. This review comprehensively summarizes and discusses the fabrication processes, structural characteristics, antibacterial performance, and the corresponding mechanisms of MoS2 ‐based materials as well as their representative antibacterial applications. In addition, the outlooks on the remaining challenges that should be addressed in the field of MoS2 are also proposed. Abstract : This review systematically summarizes the recent progress of MoS2 for photo‐excited antibacterial application, including preparation and modification methods as well as the basic photothermal and photocatalytic characteristics and corresponding mechanisms. The high specific surface area, ultra‐thin layer structure, tunable bandgap, and high photothermal conversion efficiency endow MoS2 ‐based materials with extensive antibacterial applications due to the synergy of multi‐functional bacteria‐killing modes.